Acceptability and preferences regarding cognitive rehabilitation programs for cancer-related cognitive impairment in breast cancer survivors [abstract] - Loureiro, Liliana (2024)
Introduction/ Objective: Breast cancer survivors (BCS) frequently experience cancer-related cognitive impairment (CRCI), which has a negative impact on their quality of life. Studies indicate that cognitive rehabilitation is effective at improving CRCI. However, the literature is scarce on the perspectives of this population towards these interventions. Thus, this study aimed to explore acceptability and preferences regarding cognitive rehabilitation programs for BCS reporting cognitive complaints. Method: Eighty-six women diagnosed with breast cancer (Mage = 48.7 years, SD=7.7 years; range: 31-63 years), who experienced self-reported cognitive complaints, were recruited through social networks. Participants were asked to answer an online survey with questions about sociodemographic and clinical information, pre-existing knowledge about CRCI, access to support to cope with CRCI, barriers and facilitators to participate in cognitive rehabilitation programs, and acceptability, expectations, and preferences regarding cognitive rehabilitation programs. Results: Thirty-nine percent of BCS considered having “none” (7.3%) or “little” (31.7%) knowledge about CRCI. Most participants (90.1%) reported that they “do not receive or have never received” support to deal with cognitive difficulties, mainly because they had not heard about the existence of such programs and/or received information on how to enroll in them (79.5%). For the remaining BCS (9.9%), psychological counseling was the main supportive intervention to help cope with CRCI. “Doing something to help yourself ” (62.8%) and “help to better deal with cognitive complaints” (61.5%) were identified as the main motivators for enrolling in a cognitive rehabilitation program. Considering the barriers to participating in these programs, “difficulty in finding a program/not knowing where to find help” (44.9%) and “lack of information regarding support for CRCI” (33.3%) were referred as main factors. Among several treatment options for CRCI (e.g., cognitive rehabilitation, exercise, meditation, pharmacotherapy, psychological counseling), 53.6% of participants considered cognitive rehabilitation acceptable. Regarding preferences about the characteristics of these programs, 37.1% preferred a longer program (more than 12 sessions), being held weekly (51.6%), with sessions lasting between 30 and 60 minutes (66.1%). Considering the format of these interventions, BCS preferred a face-to-face group format guided by a professional. Participation in cognitive rehabilitation programs would be “very likely” if suggested by health professionals (medical oncologist or nurse = 66.1%; general practitioner = 55.7%). Conclusions: Findings from this study support the acceptability of BCS regarding cognitive rehabilitation programs and provide information of utmost importance to inform health professionals and researchers in developing meaningful interventions to increase adherence to these programs.